2006
DOI: 10.1002/app.23875
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/poly(ethylene terephthalate) conducting composite fabric with improved fastness to washing

Abstract: In this article, we report a novel method for the design and development of a polyaniline (PANI)/poly (ethylene terephthalate) (PET) conducting composite fabric based on in situ polymerization. With the aim of improving fabric-PANI adhesion and good fastness to washing, we took some special steps: the alkali reduction pretreatment of the PET fabric before the polymerization of aniline onto the fabric, the introduction of squeezing the laboratory padder on the fabric to push the reagent into the inner part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Since the pioneering work of Gregory et al [1] different works have been published concerning the production of polypyrrole (PPy) or polyaniline (Pani) coated fabrics to produce conductive fabrics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The applications of polyaniline coated fabrics are for example as: ammonia sensor [2], electromagnetic shielding [3][4][5], static charge dissipation [4], electromechanical devices [6] or precious metals recovery [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Gregory et al [1] different works have been published concerning the production of polypyrrole (PPy) or polyaniline (Pani) coated fabrics to produce conductive fabrics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The applications of polyaniline coated fabrics are for example as: ammonia sensor [2], electromagnetic shielding [3][4][5], static charge dissipation [4], electromechanical devices [6] or precious metals recovery [7].…”
Section: Introductionmentioning
confidence: 99%
“…This acid medium is needed for obtaining polyaniline in its conducting form. Different textile substrates have been coated with polyaniline, like: polyester [1,3,6,[10][11][12][13][14][15][16][17], nylon 6 [1,2,7,10,14], wool [10,14], acrylics [10,14], cotton [5,10,14], silica [3,4], glass [3] or quartz [1]. In the present study, we have employed polyester (PES) since this synthetic polymer is not damaged by the acid media employed to carry out the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al . also reported that, to obtain a homogeneous PAn coating on PET surfaces, it was favored to use an alkali pretreated PET fiber …”
Section: Resultsmentioning
confidence: 99%
“…This restricts their use, e.g., in biomedical applications that often require good level of conductivity at physiological pH. Also the washing of textiles takes place under alkaline conditions with detrimental effect on conductivity [49,52,67]. On the other hand the reduction in the conductivity of polypyrrole nanotubes after treatment with alkalis, such as 1 M ammonium hydroxide, is low, and good level of conduction 10 −2 S cm −1 is maintained, which is much higher compared with the globular form.…”
Section: Page 4 Of 18mentioning
confidence: 99%